2014
DOI: 10.1089/lgbt.2013.0016
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward LGBT Patients Among Students in the Health Professions: Influence of Demographics and Discipline

Abstract: Health professions students with higher levels of religiosity and lower levels of self-reported familiarity with various religious perspectives on sex reported less positive attitudes toward LGBT individuals. Results suggest that personal factors may be important to address in interprofessional curriculum related to LGBT patient care. Self-report biases and other factors may limit the accuracy and generalizability of the findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 22 publications
6
47
1
Order By: Relevance
“…Similar to other samples of medical providers, [78][79][80] our survey responses suggest that provider religion and religiousness have a significant relationship to their understanding of LGBTQ patients. Unlike other samples, however, there was no reported correlation among this sample between religion or religiousness and willingness to care for LGBTQ patients 78 or knowledge of LGBTQ health.…”
Section: Role Of Religion and Religiousness In Rural Primary Caresupporting
confidence: 73%
“…Similar to other samples of medical providers, [78][79][80] our survey responses suggest that provider religion and religiousness have a significant relationship to their understanding of LGBTQ patients. Unlike other samples, however, there was no reported correlation among this sample between religion or religiousness and willingness to care for LGBTQ patients 78 or knowledge of LGBTQ health.…”
Section: Role Of Religion and Religiousness In Rural Primary Caresupporting
confidence: 73%
“…These data provide a snapshot of learning outcomes in the New England region. As provider attitudes and behaviors toward SGM patients and medical students’ experiences related to SGM health issues may vary significantly by region, additional research is needed to evaluate curricular needs in different geographic regions [24,28,3440]. Assessment of objective, rather than self-reported, learning outcomes will also be a critical component of future research in this area.…”
Section: Discussionmentioning
confidence: 99%
“…LGBT curricula content is, in other words, structurally recognized as being important for the education of culturally competent practitioners and for the creation of accessible and non-discriminatory places of work (Wilson et al, 2014). However, we found that resistances to including LGBT curricula content at the institutional level are facilitated by a lack of focus about particular LGBT issues in the policies underpinning professional healthcare practices, ranging from a lack of directed curricula focus to a dearth of local-level curricula and assessment and a lack of external monitoring or validation.…”
Section: Discussionmentioning
confidence: 99%
“…LGBT curricula content is recognized as being important for the education of culturally competent practitioners and for the creation of accessible and non-discriminatory places of work (Wilson et al, 2014). Some research (Vaid, 1995) has powerfully argued that in responding to the requirements of LGBT populations accessing health and social care, demands the use of different models which are underpinned by an extensive reformulation of LGBT healthcare curricula.…”
Section: The Historical Pathologization Of Lgbt People In Medical Hementioning
confidence: 99%